Contemporary perspectives on bereavement and pathological grief - Chaban Олег; Skrynnyk Ольга (Psychosomatic Medicine and General Practice, 2024)
Objective. Due to the war in Ukraine the problem of loss has become critical. Significant bereavement cause grief. At the core of grief is separation distress which is accompanied by loss-related experiences. They trigger a grieving process that helps adjust to bereavement and requires different strategies in different areas of life. If the burning is prolonged, it maladapts the person and pathological burning is formed. Purpose. The purpose of the article is to conduct an analysis of the concept of "normal grief" and "pathological grief", a critical review of modern researches on this problem. Methods. In order to achieve the purpose, a thorough qualitative and quantitative content analysis of scientific researches devoted to bereavement, normal and pathological grief was carried out. The article search was made using international databases such as PubMed, Google Scholar, Web of Science and CrossRef, for the period 1997-2024. Conclusions. Considering the ongoing war in Ukraine, studies related to pathological grief are relevant. In the first place are diagnostic criteria and a clear distinction between normal and pathological reactions to bereavement, identification of risk factors, detection of subtle physiological and psychological mechanisms of prolongation of the grieving process.